The Impact of Perceived Value and Customer Experience on Willingness to Pay: The Mediating Effect of Brand Image Among Coffee Shop Consumers - Sarah Permata Utami; Osly Usman (Journal of Strategic Marketing and Innovation, 2026)
Customers' willingness to pay higher prices is becoming increasingly important due to the rising competition caused by Indonesia's growing coffee shop industry. This study examines how customer experience and perceived value impact willingness to pay through brand image. The data collected from South Tangerang, Indonesia, coffee shop customers via questionnaires was analyzed using Partial Least Squares Structural Equation Modeling (PLS SEM). The findings demonstrate that perceived value and customer experience have a positive effect on brand image and willingness to pay. Apart from that, brand image plays a role in mediating these relationships, suggesting that offering better value and satisfying customer experiences can improve brand image and encourage consumers to pay higher prices.